Decision Support System for Determining the Best Wood For the Production Cabinet Using Bayes Method: Decision Support System for Determining the Best Wood For the Production Cabinet Using Bayes Method - Roimasro Sibagariang; Fristi Riandari (Jurnal Mantik, 2019)
Wood in the furniture company is a material that is needed in the manufacture of a product, for example in the manufacture of cabinets or other furniture products. Furniture companies at this time often have problems in determining wood for good quality and lack of knowledge in good wood specifications to be used as materials for making wood crafts, furniture companies only think of orders and do not consider the results of craftsmanship produced from raw materials is wood where to determine a production in order to get quality that is of a quality wood drought must be considered.